Analysis of the results of the winning diploma theses in the Competition for the Annual SARP Prize. Zbyszek Zawistowski “DIPLOM OF THE YEAR” in 2018−2022 - Stabryła, Rafał; Pytka, Alicja (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2023)
This article presents a comparative analysis of the awarded and winning diploma works in the Annual Zbyszek Zawistowski Competition for “Diploma of the Year” in 2018−2022. The comparative analysis examines the competition works in terms of functional aspects. The winners in the last five editions of the competition are diploma works with public and sacred functions. In the awarded projects, the characteristic form of the designed buildings and building complexes is the partial or complete burial of the volume of the buildings underground. In the award-winning diploma works by the competition jury, one can observe the repetition of the type of new development projects and the combination of conservation facilities with new development. Projects located in Poland predominate in the awarded diploma theses. Graduates of the Wrocław University of Science and Technology received six out of twenty awards in the Competition for the Annual SARP Award. Zbyszek Zawistowski “DIPLOM OF THE YEAR” in 2018−2022.